2015
DOI: 10.18632/oncotarget.5595
|View full text |Cite
|
Sign up to set email alerts
|

Free intraperitoneal tumor cells and outcome in gastric cancer patients: a systematic review and meta-analysis

Abstract: PurposeDespite continuously improving therapies, gastric cancer still shows poor survival in locally advanced stages with local recurrence rates of up to 50% and peritoneal recurrence rates of 17% after curative surgery. We performed a systematic review with meta-analyses to clarify whether positive intraperitoneal cytology (IPC) indicates a high risk of disease recurrence and poor overall survival in gastric cancer.MethodsMultiple databases were searched in December 2014 to identify studies on the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 98 publications
(216 reference statements)
1
31
0
1
Order By: Relevance
“…Similar to Pecqueux et al 106, our study also revealed a high level of heterogeneity for recurrence rates. This finding could be explained by the different follow-up programs of each oncologic center, including different adjuvant therapies and methodologies for diagnosing recurrence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to Pecqueux et al 106, our study also revealed a high level of heterogeneity for recurrence rates. This finding could be explained by the different follow-up programs of each oncologic center, including different adjuvant therapies and methodologies for diagnosing recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Pecqueux et al 106 also analyzed the relationship between IFCCs and survival and recurrence rates. However, they compared studies that evaluated recurrence and survival rates at different times, which compromised the validity of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Though patients were explored for metastatic disease prior to resection, routine peritoneal washings were not performed in the earlier study period. Many studies have demonstrated the association between free intraperitoneal tumor cells and poor survival and peritoneal recurrence (34)(35)(36). It is possible that LP patients had a greater likelihood of undiagnosed peritoneal disease and hence survival rates were lowered.…”
Section: Discussionmentioning
confidence: 99%
“…As for the two other gastric cancer cell strains, N87 and SGC7901 cells had elevated ANGPTL2 protein expression levels that were slightly lower compared to normal levels. The probable explanation is that the N87 and SGC7901 cell lines had a lower metastatic capacity and the BGC823 and PAMC82 cell lines had a higher degree of malignancy, which exhibited strong migratory ability[32-34]. Recent studies have reported that the carcinogenic capacity of PAMC82 cells is higher than that of N87 cells[35,36].…”
Section: Discussionmentioning
confidence: 99%